Potensi Sereal Tepung Umbi Suweg (Amorphophallus companulatus) sebagai Penurun Berat Badan pada Mencit Jantan dengan Diet Tinggi Lemak - Marta, Ayuk; Fitri Eka Lestari; Handayani, Dwi; Ardelia, Gita (LPPM-KI - POLTEKKES PIM (Formerly AKAFARMA-AKFAR PIM, 2024)
Suweg tubers (Amorphophallus companulatus) is a plant that grows wild and is widely used as fodder. The largest component in suweg tuber is carbohydrate that is 80%-85% with glukomanan. Glukomaman is a natural polysaccharide which cannot be hydrolyzed by digestive enzymes in the human body and is known as a no-calorie compounds. This study aims to determine the effect of cereal-based flour suweg tubers (Amorphophallus companulatus) against weight loss of male mice with high fat diet. Process to made flour from suweg tuber, was cleaned and chopped. Chopped then soaked with salt water then dried and powdered. The yield in flour were obtained by 5.2%. Suweg tubers flour that has been processed into cereal. Cereals made with three variations of the formula that is with the addition of 75g:25g, 50g:g50 and 75g:25g in each recipe. The result cereal flake shaped, sweet flavor, color suweg flour browned and flavorful, and the formula 1 with the addition is a formula which gives the effect of the most in reducing weight.